LEARNING EFFECTIVENESS OF THE HABITUATION AGENDA FOR BASIC TRAINING FOR CIVIL SERVANTS CANDIDATES AT BAPELKES SEMARANG - warlin, Suwarlin (Pusdiklat BMKG, 2022)
This study aims to examine the effectiveness of learning the habituation agenda for the Basic Training of Prospective Civil Servants (Latsar CPNS) at the Health Training Center (Bapelkes) Semarang in 2021. The research methods used include quantitative descriptive and hypothesis testing. The research population is the first batch III CPNS Latsar participants at Bapelkes Semarang in 2021 as many as 40 people. Primary data collection was obtained by distributing questionnaires via google form, while secondary data was obtained from training controller reports. To achieve the research objectives, data processing was carried out using excel and SPSS. The results showed that the effectiveness of habituation agenda learning was seen from the roles of coaches, mentors, and examiners who were perceived to be very capable of inspiring and motivating, participants had environmental scanning abilities, actualization of the basic values of Civil Servants underpinning activities, an increase in the value of the actualization design to actualization results. by 49.7%. From the average test with a 95% confidence level, it is believed that the mentoring carried out is able to change the average value of the actualization design up to 4.25. Suggestions for research are to find out the benefits of actualizing agenda 2 and agenda 3 which underlies activities for stakeholders and/or leaders, contributing to the achievement of the organization's vision, mission and goals, and strengthening organizational values. Keywords: the role of the coach, actualization, environmental scanning